チジョウ コウガク カンソク ニ ヨル コウカ デンシ エネルギー パラメータ ノ トクセイ オヨビ カソク キコウ スイテイ ヘノ オウヨウ - 守嶋, 圭; モリシマ, ケイ; 小野, 高幸; オノ, タカユキ; 林, 幹治; ハヤシ, カンジ; Morishima, Kei; Ono, Takayuki; Hayashi, Kanji (1993)
P(論文) 1990年第31次南極地域観測隊により昭和基地において観測された多波長フォトメータデータより, 844.6nm (OI)光, 並びに670.5nm (N_21PG)光強度を用いて推定された降下電子のエネルギーパラメータの関係を, タイプAオーロラ, パルセーティングオーロラ, ブレイクアップ時のオーロラについて調べた。解析の結果, オーロラのタイプ別に, エネルギーパラメータは異なる関係を示すことがわかった。特にディスクリートオーロラでは, 降下電子の全エネルギーフラックス(E_ )は平均エネルギー(E_ )の二乗に比例する関係(E_ =K′・E^2_ )が多く見られた。この関係はディスクリートオーロラを励起する降下電子が沿磁力線電位差で加速されるという理論的予測と一致する。実際の観測例の中には上記の比例関係が見られないディスクリートオーロラも存在するが, その原因として, (1)通過するオーロラがフォトメータの視野範囲を十分覆っていない場合, 及び(2)磁気圏側の電子密度, 温度が時間的に変動している場合があることが示された。 The relations between average energy and total energy flux of incident electrons are examined for three types of auroras, namely, type A aurora, pulsating aurora, and discrete aurora in auroral break up. The energy parameters of primary electrons are derived by using measured intensities at 844.6nm (OI) and 670.5nm (N_21PG) from a multi-channel photometer observation at Syowa Station, Antarctica, in 1990. It is shown that each auroral type has its own relationship between energy parameters of precipitating electrons. In a discrete aurora, downward electron energy flux generally varied proportionally with square of average energy. This tendency can be identified as an ohmic-like feature. This special relation is accounted for by a theory in which electrons are accelerated by a field-aligned-potential difference. We also found that in some discrete auroras, precipitating electrons did not show the ohmic-like behavior. These exceptional cases are thought to be caused by two factors. One is a geometric relation between auroral arcs and the field of view of the photometer. The other is the change of the L-E-L constant in the magnetosphere (M. FRIDMAN and J. LEMAIRE; J. Geophys. Res., 85,664,1980) due to temporal variations of plasma parameters, such as electron density and thermal energy in the source region of the auroral particles. departmental bulletin paper